Implementation of electre methods in determining for recipient candidate for pamsimas program in district pringsewu - Irviani, Rita; Mukodimah, Siti; Muslihudin, Muhammad; ., Trisnawati (International Journal of Engineering and Technology, 2018)
Community-based Water Drinking Supply and Sanitation is one of the programs implemented by the Government of Indonesia with the support of the World Bank. One of the government targets under the RPJPN 2015-2019 is that Indonesia can provide drinking water and sanitation services for the people of Indonesia. The ELECTRE method is chosen because it is able to select the best alternative from the existing alternatives. This research used seven criteria as reference in determining for recipient candidate for PAMSIMAS program. The number of incidents of diarrheal diseases in one year (number of incidents), the number of people who have not used safe drinking water (individual), the number of people who have not used the toilet, the financial ability of the region, the income of the villagers, the distance of the source of clean water from the settlement, the availability of clean water. In addition to the criteria is also used the quality of the criteria to determine the best alternative and from the calculation of the alternative obtained the greatest value contained in A4 with value E = 4 and alternative A5 with the value E =4 thereby alternatives 4 and 5 are viable alternatives to the prospective recipient villages of the PAMSIMAS program in Pringsewu district.Â Â